2014
DOI: 10.1159/000355440
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B<sub>12</sub> Deficiency in Jordan: A Population-Based Study

Abstract: Background: Vitamin B12 deficiency is highly prevalent worldwide and has been linked to hematologic, neurologic and psychiatric diseases. There are a few studies regarding vitamin B12 deficiency in developing countries in general and in Jordan in particular. Objectives: The aims of the present study were to assess the vitamin B12 status of Jordanians at national level and to identify population groups at high risk for vitamin B12 deficiency. Methods: Vitamin B12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 15 publications
4
30
3
Order By: Relevance
“…The study revealed that gender plays a role in vitamin B12 metabolism, with a twofold greater risk for deficiency among men, independent of anemia, folate, and homocysteine status. Although the prevalence is similar to the level reported in a neighboring Middle Eastern country, the gender differences are surprising [19]. …”
Section: Discussionsupporting
confidence: 68%
“…The study revealed that gender plays a role in vitamin B12 metabolism, with a twofold greater risk for deficiency among men, independent of anemia, folate, and homocysteine status. Although the prevalence is similar to the level reported in a neighboring Middle Eastern country, the gender differences are surprising [19]. …”
Section: Discussionsupporting
confidence: 68%
“…Even amongst the vegetarians and mixed diet group, the B12 deficiency was higher in men than in women (70 vs. 43% and 38 vs. 24%) despite the higher dietary intake in men. However, it should be noted that the concentration of B12 between 203 and 350 pg/ml [37,38] accompanied by elevated plasma Hcys concentration (>12 μmol/l) was considered as borderline deficiency of B12. Therefore, we have also analyzed the concentration of Hcys in the samples to confirm borderline deficiency of B12.…”
Section: Resultsmentioning
confidence: 99%
“…A reference range of 200 to 900 picogram (pg) per milliliter (ml) is commonly used for vitamin B12 concentration in the blood . Adults with lower B12 level than the lower limit of 200 pg/ml are considered B12 deficient.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these different reference ranges, recent studies revealed a prevalence of 16 to 50% B12 deficiency among Jordanians . In their most recent study, report that one‐third of jordanians are B12 deficient based on a 200 pg/ml lower limit. An urgent question to be answered is the following: what is the true reference range for normal B12 level?.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation